The Impact of Emissions-Based Taxes on the Retirement of Used and Inefficient Vehicles: The Case of Switzerland - Anna Alberini; Markus Walter Bareit; Massimo Filippini; Adan L. Martinez-Cruz (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
Many countries have adopted policies designed to reduce CO2 emissions from road vehicles. Taxes linked to the CO2 emissions rate or the fuel economy of a vehicle (which is inversely related to its CO2 emissions rate) are examples of such policies. These taxes are usually imposed on new vehicles, and previous evaluations have estimated the increases in the shares or sales of new and fuel-efficient vehicles associated with such taxes. In contrast, we ask whether taxes on new cars that penalize high emitters induce changes in the retirement of used and inefficient vehicles. We exploit natural experiment conditions in Switzerland to analyze the impact of two different “bonus”/“malus” schemes implemented at the cantonal level. In both schemes, the bonus rewards new efficient vehicles. The malus is retroactive in canton Obwalden, in the sense that it is charged on both new and existing high-emitting cars, but it is only applied prospectively to new cars in Geneva. We use a difference-in-difference design within a survival analysis setting. We find that a bonus/malus accelerates the retirement of existing high-emitting vehicles in Obwalden, shortening the expected lifetime of the three most popular make-models by 7 to 11 months. The effect is the opposite in Geneva, where we estimate that the expected lifetime of these three popular models is extended by 5 to 8 months. These findings have important implications about the desirability of bonus/malus schemes and on their design, as well as on old car scrappage programs.
Keywords: L62; Q4; Q5; 330; Vehicle retirement; Emissions-based taxes; bonus/malus; difference-in-difference; survival analysis; Switzerland; Kraftfahrzeug; Technische Effizienz; Nachfrage; Ökosteuer; Anreiz; Steuerwirkung; Konsumentenverhalten; Statistische Bestandsanalyse; Obwalden; Genf; Schweiz